Exploratory study : business-to-consumer Electronic commerce adoption issues in Singapore - Ang, Ee Teng (2008)
This research examines the motivational factors for companies to go online, the trust factors considered by companies before they go online and the Electronic Commerce Value Chain of companies who have gone online. These business-to-consumer electronic commerce adoption issues were analyzed within and across the Retail and Travel/Job Placement industries.